Emotional Intelligence and Self-Harming Behavior of Junior High School Students with Absentee Parents in a Catholic University - Lorence R. Macahilig; Chris Feli Joy P. Tajonera (Philippine Social Science Journal, 2025)
Recognizing the critical role of emotional regulation in adolescent development, this study assessed the emotional intelligence (EI) and self-harming behaviors of Junior High School students with absentee parents to inform a resilience program. Utilizing a descriptive, comparative, and correlational design, the research revealed that while respondents generally possessed very low EI, they surprisingly exhibited no risk of self-harm. Statistical analysis confirmed a significant relationship between EI and self-harm, with sex being the only demographic variable yielding significant differences in self-harming behaviors. These findings suggest that protective factors may mitigate risks despite low EI, providing a baseline for schools to develop holistic interventions; future research should employ mixed methods and broader sampling to further explore these complex dynamics.